Síntese e Caracterização da Sílica Mesoporosa SBA-16 para Aplicação na Liberação de Troxerrutina - Semião, Luana de Morais (2019)
Mesoporous silica functionalized type SBA-16 with amino groups (NH2) have been prepared to act as devices for controlled drug release. The functionalization with organic groups is carried out by two different methods, post-synthesis and co-condensation. In this work, the matrix was prepared by co-condensation and (3-aminopropyl) trimethoxysilane (APTMS) was the organoalkoxysilane used in the process of funcionalization. The synthesized materials were characterized by small angle X-ray scattering (SAXS), Solid State Nuclear Magnetic Resonance of 13C and 29Si (NMR 13C and 29Si), thermal analysis (TGA/DTG), Infrared Spectroscopy (FT-IR), Adsorption-Desorption of Nitrogen (BET) and Elemental Analysis. The SBA-16 materials had specific surface area of 575 m2 / g, total pore volume of 0.45 cm3 at relative pressures of 0. 959 (p/po). FT-IR, NMR 13C, and TG/DTG confirmed the incorporation of NH2 group into the material. The analyzes showed that all samples synthesized present cubic structure, characteristic of mesoporous materials type SBA-16, with good ordering of the pore, high surface area and narrow pore size distribution (BET). The controlled-release study showed that the surface modification has improved the release rate of the drug troxerutin compared to the material not functionalized.